The mid-term results of treatment for tibial pilon fractures - Gulabi, Deniz; Toprak, Ozgur; Sen, Cengiz; Avci, Cem Coskun; Bilen, Erkal; Saglam, Fevzi (My University, 2012)
BACKGROUND In this report, the surgical treatment results of distal tibia (pilon) fractures are analyzed radiologically and clinically. METHODS Between 2002 and 2009, 32 feet of 31 patients (25 males, 6 females; mean age 46 years; range 17 to 72 years) who were treated surgically for tibial pilon fractures were evaluated. Open reduction and internal fixation were applied to 24 and external fixation to 8 fractures. The patients were evaluated according to the Teeny-Wiss functional ankle score, and overall assessment of reduction was calculated radiographically according to the criteria of Ovadia and Beals. RESULTS While excellent results were achieved in 9 (47.4%) type 2, 5 type 1 (26.3%), and 5 (26.3%) type 3 fractures, fair/poor outcomes were obtained in 9 (69.2%) type 3 and in 2 (15.4%) types 1 and 2 fractures each (p<0.015). Compared to the external fixation application, a statistically significantly higher number of excellent and good outcomes were obtained with open reduction internal fixation application (n=3, 15.8% vs n=16, 84.2%, respectively; p<0.05). CONCLUSION If the principles of atraumatic soft tissue dissection, anatomic reduction of the joint face, stable fixation, and early mobilization of the patient are complied with in the surgical treatment of pilon fractures, successful results can be achieved. However, in type 3 fractures, even if these principles are complied with, post-traumatic arthritis is inevitable.
Keywords: tibial pilon fractures